Detection of genetic diversity aimed at developing short-term anaerobic capacity characterized by speed and acetylcholinesterase activity in female 200m runners under the age of 18 years - Nahab, Khamael; Fathi, Rafie (Journal of Physical Education, 2023)
The importance of research is highlighted in identifying genetic determinants and indicators, especially the mechanisms of some genes associated with sports training, and in this way it is possible to control changing what is included in the training environment to influence the function of genes for female runners. The research problem centered on the possibility of determining the genetic diversity of the ACE gene to determine the genetic characteristics that distinguish female runners, which would work to develop the training process in order to achieve the best sporting achievement, which contributes to expanding horizons for coaches and players alike. The research aimed to identify the alleles of the ACE gene and determine its effect on the development of short anaerobic (phosphagenous) abilities, strength characterized by speed, and the enzyme acetylcholinesterase. The researchers used the one-group experimental approach, and the research community was selected from (8) young female athletics players. Tests were conducted before and after using the exercises that were developed as a training curriculum in the playgrounds of the Ministry of Youth schools. After obtaining the results, processing them statistically, and discussing them, the researchers concluded that there were differences. Significant in favor of the post-tests in all variables. In view of this, the researchers recommended preparing training exercises for female runners and completing the 200 m as a function of genetic indicators and according to the genetic classification. Keywords: genetic diversity, short anaerobic abilities, distinctive strength at speed, acetylcholinesterase enzyme, female 200m runners.